2021
DOI: 10.1111/ijag.16262
|View full text |Cite
|
Sign up to set email alerts
|

New glass‐based binders from engineered mixtures of inorganic waste

Abstract: Aluminum is one of the most important strategic resources, but the Bayer process, typically applied for the purification of ores, leads to vast amounts of alkaline slurry waste, known as red mud. Though interesting for potential reprocessing, red mud is still predominantly stored in big slurry pools, due to high levels of toxic metals. Toxic ions can be easily immobilized by vitrification, but the high costs of this solution need to be balanced by the reuse of the obtained glass. The present paper is dedicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Alkalis could react also with atmospheric CO 2 (M. [ 22 ]). The C–O stretching signal at around 1410 cm −1 (asymmetric stretching vibration), detected after activation but not after washing, is consistent with the formation of soluble (hydrated) carbonates.…”
Section: Resultsmentioning
confidence: 99%
“…Alkalis could react also with atmospheric CO 2 (M. [ 22 ]). The C–O stretching signal at around 1410 cm −1 (asymmetric stretching vibration), detected after activation but not after washing, is consistent with the formation of soluble (hydrated) carbonates.…”
Section: Resultsmentioning
confidence: 99%
“…Hujova et al have found out that glasses from industrial residues, composed primarily of red mud, can be applied as precursors for inorganic binders, at nearly room temperature [ 11 ], by interaction with pure water or with a highly concentrated alkaline solution. In the latter case, glass is designed to undergo a substantial dissolution, followed by condensation reactions (‘polymerization’) between dissolution products.…”
Section: Introductionmentioning
confidence: 99%
“…In alkali activation, precursors dissolve in the activating medium, -consisting of a concentrated aqueous solution of alkali hydroxides or alkali silicates-where the degradation products condense and polymerise, leading to products with variable molecular structures. A three-dimensional, continuous, highly interconnected structure is available in the subset of AAMs known as "geopolymers" [15,16]. These products feature a "zeolite-like" network, i.e., they feature a specific connectivity between structural units, finding analogies in the same zeolites, in feldspar minerals, or in alkali aluminosilicate glasses [17].…”
Section: Introductionmentioning
confidence: 99%